Early nodal and paranodal disruption in autoimmune optic neuritis - Stojic, Aleksandar; Bojcevski, Jovana; Williams-Fairless, Sarah K.; Diem, Ricarda; Fairless, Richard (Journal of neuropathology and experimental neurology, 2018)
Disturbances in the nodes of Ranvier are an early phenomenon inmany CNS disorders, including the autoimmune demyelinating dis-ease multiple sclerosis (MS). Using an animal model of optic neuri-tis, a common early symptom of MS, we have investigated nodaland paranodal compartments in the optic nerve during disease pro-gression. Both nodes and paranodes, as identified by immunohisto-chemistry against sodium channels (Nav) and Caspr, respectively,were observed to increase in length during the late induction phaseof the disease, prior to onset of the demyelination and immune cellinfiltration characteristic of optic neuritis. These changes were cor-related with both axonal stress and microglial/macrophage activa-tion, and were most apparent in the vicinity of the retrobulbar opticnerve head, the unmyelinated region of the optic nerve where retinalganglion cell axons exit the retina. Using intravitreal glutamate in-jection as a model of a primary retinal insult, we demonstrate thatthis can induce similar nodal and paranodal changes. This may sug-gest that onset of neurodegeneration in the absence of demyelin-ation, as reported in several studies into the nonaffected eyes of MSpatients, may give rise to subtle disturbances in the axo-glialjunction.
Gesehen am 17.04.2020